2013
DOI: 10.1074/jbc.m113.487595
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Promyelocytic Leukemia Protein (PML) Re-patterns Energy Balance and Protects Mice from Obesity Induced by a Western Diet

Abstract: Background:The role of PML in metabolism remains largely unexplored. Results: PML ablation re-patterns energy balance in mice by promoting fatty acid metabolism. Conclusion: PML is an energy sensor that controls gene expression to regulate metabolism. Significance: Our study provides insights into a novel role of tumor suppressor PML in metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 49 publications
2
34
1
Order By: Relevance
“…PML NBdependent activation of peroxisome proliferator-activated receptor (PPAR) g co-activator-1a (PGC-1a), PPAR signaling and fatty acid β-oxidation provided a growth advantage to breast cancer cells (Carracedo et al, 2012) and controlled asymmetric division and maintenance of hematopoietic stem cells . In contrast, PML KO mice had tissue-specific enhancement of both fatty acid b-oxidation and synthesis, increased metabolic rate and resistance to diet-induced obesity (Cheng et al, 2013). Together with these findings, our results suggest that LAP domains associated with nLDs could have a multi-facetted role in lipid homeostasis involving the recruitment of CCTa and Lipin1 to promote PC and TAG synthesis and storage as well as…”
Section: Discussionsupporting
confidence: 67%
“…PML NBdependent activation of peroxisome proliferator-activated receptor (PPAR) g co-activator-1a (PGC-1a), PPAR signaling and fatty acid β-oxidation provided a growth advantage to breast cancer cells (Carracedo et al, 2012) and controlled asymmetric division and maintenance of hematopoietic stem cells . In contrast, PML KO mice had tissue-specific enhancement of both fatty acid b-oxidation and synthesis, increased metabolic rate and resistance to diet-induced obesity (Cheng et al, 2013). Together with these findings, our results suggest that LAP domains associated with nLDs could have a multi-facetted role in lipid homeostasis involving the recruitment of CCTa and Lipin1 to promote PC and TAG synthesis and storage as well as…”
Section: Discussionsupporting
confidence: 67%
“…Using human biopsy materials and an obese mouse model, Carracedo and Pandolfi et al found that hepatic PML protein levels are increased in obese subjects which strongly correlated with liver steatosis, suggesting a role for PML in hepatic function in response to obese conditions [ 117 ]. Indeed, an earlier study by Cheng and Kao demonstrated that the depletion of Pml in mice decreases liver fatty acid accumulation after long-term Western diet feeding and in turn protects mouse liver from dysplastic nodules [ 118 ]. Dysplastic nodules are histologically visible benign lesions which follow liver steatosis and are viewed as an early stage of cirrhosis and hepatocellular carcinoma (HCC).…”
Section: Physiological and Pathological Role Of Pmlmentioning
confidence: 99%
“…Analyses of the microarray data in PML -depleted HUVECs suggest that PML is involved in the regulation of a large cohort of metabolic gene expression [ 115 , 120 ]. Along the same line, loss of Pml in mice re-patterns glucose and fatty acid metabolism gene expression in metabolically active tissues, such as muscle and liver, increases metabolic rate and resists obese symptoms induced by a Western diet [ 118 ]. It is worthy to note that different results in PML metabolic function and obese predisposition have also been reported [ 115 , 121 ].…”
Section: Physiological and Pathological Role Of Pmlmentioning
confidence: 99%
“…The PML protein and PML bodies have been shown to function in a number of processes relevant to myogenesis. For example, though skeletal muscle development is not markedly affected in Pml−/− mice, expression of muscle metabolic genes is altered, as is the regulation of cell growth and the retinoic acid pathway [34, 35]. It may be of particular relevance that PML is a regulator of p53-mediated cell death [36].…”
Section: Discussionmentioning
confidence: 99%